ZnS coating of cathode facilitates lean‐electrolyte Li‐S batteries. Issue 2 (16th October 2019) - Shin, Woochul; Lu, Jun; Ji, Xiulei
Abstract: Tremendous effort has been devoted to lithium‐sulfur batteries, where flooded electrolytes have been employed ubiquitously. The use of lean electrolytes albeit indispensable for practical applications often causes low capacity and fast capacity fading of the sulfur cathode; thus, the electrolyte/sulfur active mass ratios below 5 µL/mg have been rarely reported. Herein, we demonstrate that ZnS coating transforms sulfur cathode materials electrolyte‐philic, which tremendously promotes the performance in lean electrolytes. The ZnS‐coated Li2 S@graphene cathode delivers an initial discharge capacity of 944 mAh/g at an E/S ratio of 2 µL/mg at the active mass loading of 5.0 mg Li2 S/cm 2, corresponding to an impressive specific energy of 500 Wh/kg based on the mass of cathode, electrolyte, and the assumed minimal mass of lithium metal anode. Density functional theory calculations reveal strong binding between ZnS crystals and electrolyte solvent molecules, explaining the better wetting properties. We also demonstrate the reversible cycling of a hybrid cathode of ZnS‐coated Li2 S@graphene mixed with VS2 as an additive at an E/AM (active mass) ratio of 1.1 µL/mg, equivalent to the specific energy of 432 Wh/kg on the basis of the mass of electrodes and electrolyte. Abstract : We report that ZnS coating transforms the Li2 S@graphene electrode electrolyte‐philic. The enhanced wettability facilitates high performance of the sulfur electrode under lean‐electrolyte conditions.